2007
DOI: 10.1007/s10620-007-9803-7
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori May Play a Contributory Role in the Pathogenesis of Primary Sclerosing Cholangitis

Abstract: Helicobacter pylori (H. pylori) DNA has been identified in human livers and has been implicated in chronic liver disease and liver cancer. To better understand the role of H pylori in primary sclerosing cholangitis (PSC), 25 patients with end-stage PSC and 31 controls were studied. Genomic DNA was extracted from microdissected hilar hepatic ducts of liver explants and was amplified for H pylori DNA. Serum was tested for H pylori antibodies. Helicobacter DNA was detected in 9 of the 56 (16%) patients by 16SrRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 22 publications
1
21
0
1
Order By: Relevance
“…Such assertion, however, is diffi cult because the concept of eosinophilic cholangitis is still confused, and some papers seem to report IgG4-related SC with eosinophilia as eosinophilic cholangitis. 17,18 We also examined H. pylori infection, which is a possible pathogenesis of PSC, 19 We are skeptical of the pathogenicity of H. pylori, however, because infection was recognized in only two patients in the older group.…”
Section: Discussionmentioning
confidence: 99%
“…Such assertion, however, is diffi cult because the concept of eosinophilic cholangitis is still confused, and some papers seem to report IgG4-related SC with eosinophilia as eosinophilic cholangitis. 17,18 We also examined H. pylori infection, which is a possible pathogenesis of PSC, 19 We are skeptical of the pathogenicity of H. pylori, however, because infection was recognized in only two patients in the older group.…”
Section: Discussionmentioning
confidence: 99%
“…have been reported by Fox et al [10], who have shown the presence of H. bilis and H. pullorum in the bile of Chilean patients with chronic cholecystitis. Recently, Helicobacter DNA has been found in the liver of patients with different chronic liver diseases (CLD), such as primary sclerosing cholangitis (PSC) [11], hepatocellular carcinoma (HCC) [12], hepatitis C virus (HCV)-related chronic hepatitis, and cirrhosis [13,14]. CLD is an inflammatory disease and each inflammatory process is characterized by increased levels of pro-inflammatory cytokines, such as interleukins 1 and 6 (IL-1 and IL-6), tumor necrosis factor (TNF), and by the presence of lympho-mono cellular infiltrate and lymphoid follicle formation [12].…”
Section: Introductionmentioning
confidence: 99%
“…H. pylori infect more than 50% of humans globally with a prevalence of 25% in the developed countries and more than 90% in the developing countries [1]. It has been generally accepted that H. pylori cause gastric and duodenal ulcer diseases, primary B-cell gastric lymphoma, and sclerosing cholangitis [2,3]. H. pylori virulence factors play an important role as the virulent strains of H. pylori increase the risk of developing more severe clinical manifestations.…”
mentioning
confidence: 99%